Presidential Authority and National Legal Policy Formation: A Comparative Constitutional Analysis of Indonesia and the United States - I Gede Putu Sentana Wirayoga; I Gede Pasek Eka Wisanjaya (International Journal of Business, Law, and Education, 2026)
Presidential systems allocate executive and legislative authority through different constitutional arrangements, yet the practical capacity of a president to shape national legal policy cannot be inferred from formal powers alone. This article compares presidential authority in Indonesia and the United States by examining four dimensions of legal-policy capacity: agenda initiation, participation in ordinary legislation, unilateral rule-making, and institutional control. Using normative legal research and a functional comparative-law method, the study analyzes constitutional provisions, legislation, constitutional jurisprudence, and relevant scholarship on presidentialism and executive–legislative relations. The analysis shows that the Indonesian President operates as a constitutionally integrated co-legislator. Although the House of Representatives formally holds legislative power, bills require joint deliberation and approval, while the President may initiate bills and issue government regulations in lieu of law under constitutionally specified emergency conditions. By contrast, legislative power in the United States is vested in Congress, and the President primarily shapes statutes through agenda leadership, partisan bargaining, presentment and veto, and administrative directives. The difference is therefore not a simple contrast between a strong and a weak presidency. Indonesia concentrates presidential influence within the ordinary legislative process and multiparty coalition bargaining, whereas the United States channels presidential influence through interbranch bargaining and unilateral administration constrained by statutes, Congress, courts, and bureaucratic implementation. The article argues that democratic legal-policy formation requires not merely balanced textual powers, but also transparent coalition management, meaningful public participation, reasoned emergency lawmaking, and effective legislative and judicial review.